Transformation of Lifestyle, Social Structure, and Family Economy of Cruise Ship Workers (Case Study in Lajing Village, Arosbaya Subdistrict) - Miftahul Amaliyah; Yusrianto Sholeh (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze the transformation of lifestyle, social structure, and economy of cruise ship workers' families in Lajing Village, Arosbaya District, Bangkalan Regency. The research method used is descriptive qualitative with a phenomenological approach. Data were collected through in-depth interviews with cruise ship workers and their family members, as well as observation and documentation. The results of the study show that working on cruise ships has a significant impact on changes in lifestyle, social structure and family economy. Increased income enables families to improve their quality of life, meet their needs and achieve their dreams. However, this change also brings its own challenges, such as changing roles in the family and changing consumption patterns. This research highlights the importance of a deeper understanding of the social and economic dynamics that occur in cruise ship workers' families, so that it can contribute to the development of better policies to support the welfare of migrant workers' families.